Participants' Comprehension of the Informed Consent in an Epidemiological Study on Dementia Prevalence: A Qualitative Study - Falvo, Ilaria; Fiordelli, Maddalena; Amati, Rebecca; Ibnidris, Aliaa; Albanese, Emiliano; Fadda, Marta (Frontiers in Psychiatry, 2021)
Aim: In the absence of an effective treatment, informed participation in dementia research can hardly be underestimated. However, although informed consent is key in biomedical research, it may become a barrier to participation. Whether informed consent may cause confusion and contribute to unfair participant selection in dementia research is not known. In preparation of a future epidemiological study on the prevalence and impact of dementia in Switzerland, we aimed to conduct a qualitative study to explore participants’ comprehension of the purpose of informed consent form and process shortly after participation in the pilot and validation study that preceded the large scale survey. Methods: We conducted a qualitative study with 22 participants of the validation phase of an epidemiological study on the prevalence and impact of dementia in Switzerland to capture their understanding of both the nature and the content of the informed consent form and process. Participants were older adults (65 years or more) eligible for a dementia epidemiological study and their informant (a person who could provide information on their health and cognition). None of the participants reported to be suffering from dementia at the time of the interview. Results: We found that participants held inaccurate and potentially trust-threatening beliefs regarding the scope of the informed consent. Participants identified contradictory contextual, formal and content needs that are difficult to be fulfilled, and misperceived the clinical and research settings in terms of informed consent procedures. Conclusions: Participants and their proxies should be informed about both the scope of the informed consent process, and the content of the informed consent document in a focused, age-appropriate manner, while dispelling confusion about the purpose of research.